The Effect of Geographical Factors on Islamic Banking Sustainability Performance: An Instrumental Variable Quantile Regression Analysis - Budiman, Teguh; Febrian, Erie; Azis, Yudi (Asian Economic and Financial Review, 2022)
There is an ongoing debate on how Islamic banks contribute to bank sustainability. Theoretically, Islamic ethics promote sustainability, also called Maqasid al-shari’ah. This paper investigates the effect of geographical factors on Islamic bank sustainability. A theoretical and empirical model was developed to assess this relationship. It was hypothesized that geographical factors affect Islamic bank sustainability. Countries in specific geographical locations that are dominated by Islamic rules, such as the Middle East, have different magnitudes compared to east Asian countries that have fewer Islamic rules. A geographical risk model was developed according to the Maqasid al-Shari’ah concept and was employed based on a microeconomic banking model that portrays a variety of risks for 159 Islamic banks in ten countries. We constructed variables from macroeconomic databases, such as the World Development Indicators, and microeconomic databases, such as financial indicators and environmental, social, and governance (ESG) data from Thomson Reuters from 2012 to 2019. The analysis was conducted using panel instrumental variable regression to test the hypothesis; however, geographical risk variables produced biased results affecting Maqasid financing. The method was refined with IV quantile regression. It was found that geographical factors are strongly related to the improvement of Maqasid financing in Middle East regions, whereas in eastern regions this is vice versa. The results indicate that geopolitical factors stimulate Maqasid financing for Sustainable Development Goals.